2019
DOI: 10.1007/s42452-019-1057-4
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal removal from industrial effluent using bio-sorbent blends

Abstract: There is extensive literature on the use of adsorbents derived from waste to treat industrial effluents containing heavy metal ions. However, there is limited information on the use of adsorbent blends. This is applicable for treating effluents which contain a number of heavy metals, so any one single adsorbent may not be suitable for achieving high percent removal of all ions. The present work employs adsorbent blends to treat an electrochemical effluent in batch mode. This work aims to provide valuable insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…The findings of this study demonstrate that the adsorption of chromium (VI) ions onto groundnut shell-based biomass is most rapid with an excess of binding sites and gradually slows down as the proportion of binding sites declines. This is similar to the trends observed by other researchers who discovered that most adsorption occurred in the first 35 minutes of exposure of the biosorbent to industrial effluent (Sreedhar & Reddy 2019;Ahamad et al, 2019). At low metal ion loads, adsorption involves high-energy sites.…”
Section: Effect Of Biosorbent Pre-treatment On Biosorption Performancesupporting
confidence: 91%
“…The findings of this study demonstrate that the adsorption of chromium (VI) ions onto groundnut shell-based biomass is most rapid with an excess of binding sites and gradually slows down as the proportion of binding sites declines. This is similar to the trends observed by other researchers who discovered that most adsorption occurred in the first 35 minutes of exposure of the biosorbent to industrial effluent (Sreedhar & Reddy 2019;Ahamad et al, 2019). At low metal ion loads, adsorption involves high-energy sites.…”
Section: Effect Of Biosorbent Pre-treatment On Biosorption Performancesupporting
confidence: 91%
“…Adeleke et al (2017) demonstrated this claim by observing a decreasing pattern of heavy metal uptake as activated carbon content increases. Sreedhar and Reddy (2019) also noticed a similar decreasing trend of adsorption capacity when the adsorbent dosage was increased. The effect is probably due to the concentration gradient and increased blockage of available active sites caused by the agglomeration of GB particles that reduces the specific surface area of the sample.…”
Section: Aas Analysissupporting
confidence: 54%
“…Adding a high dosage of ground biochar pine sawdust during sample preparation provides more potential for treating POME as a higher tendency of heavy metal ions adhered to the free pore sites, allowing a greater adsorption rate. However, a few researchers have argued that further increasing the weight percentage of adsorbent will not further influence the removal percentage of heavy metals as it has already reached saturation (Pertile et al 2021;Sreedhar and Reddy 2019;Gupta et al 2021). Adeleke et al (2017) demonstrated this claim by observing a decreasing pattern of heavy metal uptake as activated carbon content increases.…”
Section: Aas Analysismentioning
confidence: 99%
“…The percent of Ni(II) adsorbed by coir pith from an effluent containing 145 mg/L of Ni(II) was 88% at 5% (w/v) adsorbent dosage and a further increase in sorbent dosage did not increase nickel removal [ 43 ]. The low rate of Ni(II) removal with the increase in sorbent dosage can be explained by sorbent particle agglomeration, which reduces the specific surface area and increases the diffusion path length [ 44 ]. In batch experiments, it was shown that with the increase in Ni(II) concentration in solution, its removal significantly decreases from 90% at Ni(II) concentration 10 mg/L to 28% at Ni(II) concentration in solution 100 mg/L.…”
Section: Discussionmentioning
confidence: 99%